Chronic low-dose rate irradiation induces transient hormesis effect on cyanobacterium Limnospira indica - Jana Fahrion; Surya Gupta; Felice Mastroleo; Claude Gilles Dussap; Natalie Leys (iScience)
Summary: Cultures of Limnospira indica were exposed to low-dose rate γ-irradiation for 8 weeks to simulate 2 months of a Mars transit irradiation. Two experiments were conducted: in the first, 5% v/v inoculations were used over 2-week batches; in the second, 25% v/v inoculations over 1-week batches. The cultures were continuously illuminated (45 μmol photons m−2 s−1, LEDs). A transient hormesis effect was observed in experiment 1, with irradiated cultures showing higher dry weight (1.88 ± 0.05 g L−1) than controls (1.70 ± 0.06 g L−1) on day 14. Irradiated cultures also had fewer pigments. Experiment 2 showed similar, though less pronounced, results. These findings suggest that Limnospira indica would not be negatively affected by cosmic radiation during Mars transit, though further validation under space flight conditions is needed. The resilience of Limnospira indica to chronic low-dose radiation supports its potential for oxygen and food production in life support systems for manned space missions.